Optimum Feeder Routing and Distribution Substation Placement and Sizing using PSO and MST - Hasan, Ihsan Jabbar; Gan, Chin Kim; Shamshiri, Meysam; Ab Ghani, Mohd Ruddin; Omar, Rosli (Indian Society for Education and Environment, 2014)
A long term distribution network planning consists of several complexity aspects due to the multiple decision variables in objective functions. Optimum placement of distribution substations and determination of their sizing and feeder routing is one of major issues of distribution network planning. This paper proposes an algorithm to find the optimum distribution substation placement and sizing by utilizing the PSO algorithm and optimum feeder routing using modified MST. The proposed algorithm has been evaluated on the distribution network case with 500 consumers which are consisting of residential and commercial loads. The test network is generated by fractal based distribution network generation model software tool. The results indicate the proposed algorithm has been succeeded to find the reasonable placement and sizing of distributed generation with adequate feeder path.